Tiny Needles Offer a Potential Long-lasting Treatment for Retinal Disease - Wadhwani, Dr. Ashish D (Asian Journal of Pharmaceutics (AJP), 2019)
Glaucoma and corneal neovascularization which is the world leading eye disease could be given new treatment options by use of tiny microneedles which are small enough to an unaided eye. Microneedles range in length from 400 to 700 Î¼m could provide a better medium of drug delivery into the eyes and thereby better disease management. The microneedle technology of drug delivery will be targeting specific to the eye and there by decrease the quantity of the drug and increase the effectiveness with minimal side effects. One of the leading causes of blindness is glaucoma, which happens when untreated and corneal neovascularization, causes an additional growth of blood vessels that damage the vision. Development of microneedle-based systems is being experimented with a way where the drug is precisely put into the part of the eye. Thus, coupling this delivery with a controlled release formulation may allow treating a condition for weeks or months. Thus, this review elucidates on the current research and the design which may act as a potential treatment for retinal disease.